Educational standards -- terminologies used. - Engelbrecht, Rolf; Ingenerf, Josef; Reiner, Jörg (Studies in health technology and informatics, 2004)
Efficient and effective delivery of health care requires accurate and relevant knowledge, patient-centred clinical data and medical information which is available to different actors and institutions in health care. Sharing data and knowledge means understanding the underlying concepts, terms, etc. Therefore a basic requirement in medical education is terminology, coding and classification. Vocabularies, data sets, schemes are to be used for medical documentation, medical statistics, analysis and system operation. Communication between heterogeneous environments will be possible when common terminologies etc. are available and used during system development. The following chapters give an overview on this important field of health telematics.